2016
DOI: 10.1152/ajpheart.00176.2016
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the hypothalamic arcuate nucleus increases brown adipose tissue nerve activity via hypothalamic paraventricular and dorsomedial nuclei

Abstract: Hypothalamic arcuate nucleus (ARCN) stimulation elicited increases in sympathetic nerve activity (IBATSNA) and temperature (TBAT) of interscapular brown adipose tissue (IBAT). The role of hypothalamic dorsomedial (DMN) and paraventricular (PVN) nuclei in mediating these responses was studied in urethane-anesthetized, artificially ventilated, male Wistar rats. In different groups of rats, inhibition of neurons in the DMN and PVN by microinjections of muscimol attenuated the increases in IBATSNA and TBAT elicite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 63 publications
(92 reference statements)
1
9
0
Order By: Relevance
“…Chitravanshi et al. more directly observed that arcuate nucleus stimulation elicited increases in sympathetic nerve activity and stimulated thermogenesis in IBAT . We also observed that small amounts of fat emulsion (intralipid) applied to the tongue stimulated sympathetic nerve activity innervated to IBAT in urethane anesthetized rats (unpublished data).…”
Section: Discussionsupporting
confidence: 72%
“…Chitravanshi et al. more directly observed that arcuate nucleus stimulation elicited increases in sympathetic nerve activity and stimulated thermogenesis in IBAT . We also observed that small amounts of fat emulsion (intralipid) applied to the tongue stimulated sympathetic nerve activity innervated to IBAT in urethane anesthetized rats (unpublished data).…”
Section: Discussionsupporting
confidence: 72%
“…Thereby, they can adapt numerous processes in the integrated regulation of whole-body metabolism, including control of hepatic glucose metabolism and VLDL secretion, BAT activation, and adipose tissue lipolysis, (Balthasar et al, 2004; Berglund et al, 2012; Kőnner et al, 2007; Parton et al, 2007; Ruud et al, 2017; Scherer et al, 2011, 2016; Shin et al, 2017; Steculorum et al, 2016). Importantly, POMC neurons have been demonstrated to promote sympathetic nerve activation in response to leptin and insulin (i.e., in control of SNA in various tissues) (Bell et al, 2018; Chhabra et al, 2017; Chitravanshi et al, 2016; Rahmouni et al, 2003). Although our experiments clearly reveal that chemogenetic POMC neuron activation is sufficient to rapidly induce hepatic SNA and that optogenetic POMC neuron activation promotes S6 phosphorylation and Xbp1 splicing, they do not rule out the possibility that the concomitant inhibition of AgRP neuron activity may also contribute to these effects upon sensory food perception.…”
Section: Discussionmentioning
confidence: 99%
“…However, selective restoration of MC 4 R expression in the PVN of MC 4 R -null mice failed to normalize resting oxygen consumption [37], and chemogenetic activation of MC 4 R neurons in the PVN had no effect on oxygen consumption [38]. On the other hand, MC 3 R/MC 4 R blockade in the PVN was recently reported to blunt the increase in BAT SNA and BAT temperature in adult male Wistar rats microinjected with N-methyl-D-aspartate (NMDA) in the ARC [39]. In this report, energy expenditure was not measured.…”
Section: Arc → Paraventricular Nucleus Of the Hypothalamus (Pvn) Connmentioning
confidence: 99%
“…Chitravanshi et al [39] injected FluoroGold into the DMH and observed retrograde labeling of ARC neurons. Neuronal labeling demonstrated that 30 to 40% of all POMC-positive neurons, α-MSH-positive neurons and Vglut3-positive neurons contained FluoroGold.…”
Section: Arc → Dorsomedial Nucleus Of Hypothalamus (Dmh) Connectionmentioning
confidence: 99%